KOMPLEKSITAS PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL TERHADAP KONVERGENSI PRODUK DIGITAL DALAM EKOSISTEM PELATIHAN ONLINE - Sofwan Rizko Ramadoni; Rika Aulia Sari (The Juris, 2025)
The rapid growth of the online training industry (e-course) in Indonesia has created high-value digital economic commodities. However, the current Intellectual Property Rights (IPR) framework tends to view protection objects in silos, whereas an online training product is fundamentally a complex convergence of various digital elements. This study aims to dissect the legal construction of IPR protection regarding the online training ecosystem, which comprises Learning Management Systems (LMS), teaching modules, audiovisual content, and teaching methods (SOPs). This research employs a normative juridical method with statutory and conceptual approaches. The findings reveal that the online training ecosystem involves overlapping legal regimes. While videos and modules receive automatic Copyright protection, LMS intersects with Computer Program Copyright. A critical complexity arises in protecting "teaching methods" and SOPs; Trade Secret claims become weak once the material is taught to the public, while Copyright does not protect ideas or methods (idea-expression dichotomy). This fragmentation renders law enforcement against training product piracy ("access piracy") suboptimal. The study concludes that a hybrid protection strategy integrating various IPR instruments and robust contractual licensing clauses (Terms of Service) is essential to protect creators' intellectual assets comprehensively.